Desalination using a parabolic-trough concentrator - Saettone Olschewski, Erich Arturo (2012)
There are presented desalination results by using a parabolic-trough concentrator (PTC) device of 5.5 m2, 0.7 m of line focal distance and aligned in the East—West direction. The length of the PTC is 2.5 m and its rectangular absorber cavity has 1m length made of black aluminum. The equipment is located in Cocayalta (48 km from Lima, with 700–850 W/m2) and there were made simple modifications on the cavity to increase the fresh water production, from 3250 cm3 (3.25 liters) using the simplest model to 6360 cm3 (6.36 liters) with the thermal insulation and wind protection model, that represents an increase of about 95%. Finally, water analysis showed a good quality of the fresh water obtained.